PERSEPSI WAJIB PAJAK ORANG PRIBADI ATAS PERUBAHAN PTKP DAN TARIF PAJAK SERTA PENGARUHNYA TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Juita Tanjung (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2016)
The change of tax regulations often creates hesitation to people. The low level of awareness to these changes resulting to apathetic attitude that people tend to ignore the obligation as a tax payer. A research would be interesting and useful when identifying about people perception against to the change of tax regulations, in this case is income tax. Perception can be used as a measurement on how people assess the problems or changes. A positive perception to the change of "Undang-undang Pajak Penghasilan" related to the change of "Penghasilan Tidak Kena Pajak dan Tarif" is expected hence it can increase the compliance level from each tax payer. By utilization sample of respondent, that is, 52 persons, this research examines whether or not tax payer perception towards changes in Tax Allowance and Tariff Taxes has impact on the nature of their tax payment on regular basis. Obtained data are processed using double-sided regression with the assistance of SPSS 22 computer program. The research shows significant result as much as 0,032 or < 0,05 which means that there is impact of perception about those changes in Tax Allowance to the nature of their tax payment. As regards to perception towards changes in tariff taxes, it has significant result as much as 0,746 or > 0,05 which means that there is no impact of perception to the nature of their tax payment.